(Re)examining the Relationship Between Children’s Subjective Wellbeing and Their Perceptions of Participation Rights - Lloyd, Katrina (Child Indic Res, 2016)
In recent years wellbeing has been linked increasingly with children’s rights, often characterised as central to their realisation. Indeed it has been suggested that the two concepts are so intertwined that their pairing has become something of a mantra in the literature on childhood. This paper seeks to explore the nature of the relationship between wellbeing and participation rights, using a recently developed ‘rights-based’ measure of children’s participation in school and community, the Children’s Participation Rights Questionnaire (CPRQ), and an established measure of subjective wellbeing – KIDSCREEN-10. The data for the study came from the Kids’ Life and Times (KLT) which is an annual online survey of Primary 7 children carried out in Northern Ireland. In 2013 approximately 3800 children (51 % girls; 49 % boys) from 212 schools participated in KLT. The findings showed a statistically significant positive correlation between children’s overall scores on the KIDSCREEN-10 subjective wellbeing measure and their perceptions that their participation rights are respected in school and community settings. Further, the results indicated that it is the social relations/autonomy questions on KIDSCREEN-10 which are most strongly related to children’s perceptions that their participation rights are respected. Exploration of the findings by gender showed that there were no significant differences in overall wellbeing; however girls had higher scores than boys on the social relations/autonomy domain of KIDSCREEN-10. Girls were also more positive than boys about their participation in school and community. In light of the findings from this study, it is suggested that what lies at the heart of the relationship between child wellbeing and children’s participation rights is the social/relational aspects of both participation and wellbeing.